Kecerdasan logis matematis siswa yang memiliki kemampuan komunikasi matematis tinggi pada sistem persamaan linier tiga variabel - Lanya, Harfin; Zahroh, Halimatus; Zayyadi, Moh; Anjarani, Devie Reztia (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2023)
Mathematical logical intelligence greatly influences students' ability to solve mathematical problems, especially the ability to analyze logically in solving mathematical problems. This logical-mathematical intelligence is also closely related and has a positive impact on students' mathematical communication skills, both oral and written mathematical communication abilities. Based on the age development, MA students should be able to use logical thinking skills well. Through material students are tested and required to understand questions in the form of story questions to be able to solve the problem by first forming a mathematical model and then developing a plan to solve the problem. Thus, students indirectly get a stimulus to hone their reasoning and communication skills well. This study aims to analyze the mathematical logical intelligence of MA students with high mathematical communication skills on System of Linear Equations in Three Variable at MA Al-Islamiyah I Sumber Batu, Blumbungan, Larangan, Pamekasan. This type of research is qualitative descriptive research. The research instruments used were test questions and interview guidelines. The results showed that students who have high mathematical logical intelligence also have good competence for oral and written communication and are able to classify, compare, perform calculations correctly, reason deductively, make conclusions and check back according to the indicators in mathematical logical intelligence.